Enzymatic Production of Chondroitin Oligosaccharides and Its Sulfate Derivatives - Zhang, Weijiao; Xu, Ruirui; Jin, Xuerong; Wang, Yang; Hu, Litao; Zhang, Tianmeng; Du, Guocheng; Kang, Zhen (Frontiers in Bioengineering and Biotechnology, 2022)
Chondroitin sulfate (CS) has a wide range of physiological functions and clinical applications. However, the biosynthesis of chondroitin oligosaccharides (o-CHs) and sulfate derivatives with specific length is always challenging. Herein, we report enzymatic strategies for producing homogeneous o-CHs and its sulfate derivatives from microbial sourced chondroitin. Chondroitin disaccharides, tetrasaccharides, hexasaccharides, octasaccharides and decasaccharides with defined structure were produced by controllably depolymerizing microbial sourced chondroitin with an engineered chondroitinase ABC I. The highest conversion rates of the above corresponding o-CHs were 65.5%, 32.1%, 12.7%, 7.2% and 16.3%, respectively. A new efficient enzymatic sulfation system that directly initiates from adenosine 5′-triphosphate and sulfate (ATP) was developed and improved the sulfation of chondroitin from 8.3% to 85.8% by optimizing the temperature, sulfate and ATP concentration. Except for disaccharide, o-CHs decasaccharide, octasaccharide, hexasaccharide and tetrasaccharide were modified and the corresponding sulfate derivatives with one sulfate group were prepared. The enzymatic approaches constructed here for preparing o-CHs and its sulfate derivatives pave the way for the study of structure-activity relationship and applications.